Shaping the evolutionary tree of green plants: evidence from the GST family. Issue 1 (December 2017) - Monticolo, Francesco; Colantuono, Chiara; Chiusano, Maria
Abstract Glutathione-S-transferases (GSTs) are encoded by genes belonging to a wide ubiquitous family in aerobic species and catalyze the conjugation of electrophilic substrates to glutathione (GSH). GSTs are divided in different classes, both in plants and animals. In plants, GSTs function in several pathways, including those related to secondary metabolites biosynthesis, hormone homeostasis, defense from pathogens and allow the prevention and detoxification of damage from heavy metals and herbicides. 1107 GST protein sequences from 20 different plant species with sequenced genomes were analyzed. Our analysis assigns 666 unclassified GSTs proteins to specific classes, remarking the wide heterogeneity of this gene family. Moreover, we highlighted the presence of further subclasses within each class. Regarding the class GST-Tau, one possible subclass appears to be present in all the Tau members of ancestor plant species. Moreover, the results highlight the presence of members of the Tau class inMarchantiophytes and confirm previous observations on the absence of GST-Tau inBryophytes and green algae. These results support the hypothesis regarding the paraphyletic origin ofBryophytes, but also suggest thatMarchantiophytes may be on the same branch leading to superior plants, depicting an alternative model for green plants evolution.